LONG TERM SPATIO-TEMPORAL VARIATIONS OF URBAN ENERGY FLUXES USING EARTH OBSERVATION DATA FOR DELHI - M. Bondada; K. Gupta; A. Danodia; M. M. Bhatt; N. R. Patel (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
The rapid urbanization and population growth in Delhi have led to significant changes in the land and land cover, resulting in increased emissions and alterations in the urban energy balance. To understand these long-term trends and identify contributions factors, a study was conducted using Landsat series data and meteorological data from the ECMWF ERA-5 reanalysis. The study focused on estimating urban energy fluxes, including Net Radiation, Sensible heat flux, Latent heat flux and Ground heat flux with anthropogenic heat considered as the residual. The findings reveal a substantial increase in the anthropogenic heat flux, rising from 172 W/m2 in 1990 to 281 W/m2 in 2022. Seasonal variations were also observed, with the highest energy flux values occurring during the summer season, followed by post monsoon and winter season. Net radiation ranged from 650 to 700 W/m2, sensible heat flux ranged between 250–300 W/m2, latent heat flux ranged between 250–300 W/m2 and ground heat flux ranged 30–120 W/m2. Urban areas exhibited higher energy fluxes, emphasizing the importance of effective planning interventions to mitigate emissions in such areas. The study highlights the potential of Earth observation based approaches in estimating and balancing urban energy fluxes, while also emphasising the need to consider seasonal and spatial variations in the land use pattern when formulating strategies to mitigate emissions in the urban areas.